Dominica - Country Procurement Assessment Report : Volume 2. Data and Analysis - World Bank (Washington, DC, 2013)
Due to the size of the country, the Government of Dominica carries out limited amounts of procurement, with the majority of capital investments being financed by external sources. However, the domestic public sector procurement system is inefficient and lacks transparency posing a high fiduciary risk. The lack of transparency itself is a major cause for inefficiency and excess costs and has a significant negative impact on trade, investment, and economic growth. This Country Procurement Assessment Report includes stand-alone, short, and medium-term recommendations which would enhance transparency and efficiency in the domestic procurement environment independently of the regional harmonization effort. However, given the small size of Dominica's economy, limited amount of procurement, and scarce human resources, real economies of scales with respect to operational procurement as well as overall capacity can be best achieved by framing medium-term recommendations in terms of regional approaches.